Elevated 68Ga Prostate-Specific Membrane Antigen Activity in Metastatic Non–Small Cell Lung Cancer. (May 2016) - Shetty, Deepa; Loh, Han; Bui, Chuong; Mansberg, Robert; Stevanovic, Amanda
Abstract : Abstract: A 71-year-old man with a background of treated stage IIIB non–small cell lung cancer was referred for 68 Ga prostate-specific membrane antigen (PSMA) PET/CT for staging of prostate cancer. In addition to the PSMA uptake in the known prostate malignancy, the study also demonstrated increased PSMA uptake in an enlarging left lower lobe lung mass with diffusely increased PSMA uptake in an enlarged thyroid gland and bilateral enlarged supraclavicular lymph nodes. Fine-needle aspiration biopsy of the thyroid gland and a left supraclavicular lymph node demonstrated metastatic adenocarcinoma from a primary lung cancer.